CO2 Conversion by Fischer‐Tropsch Synthesis Using Na‐Modified Fe Catalysts. Issue 11 (7th September 2022) - Schmidt, Christian; Kureti, Sven
Abstract: Three Fe catalysts with different Na contents were prepared, characterized, and investigated for the CO2 ‐based Fischer‐Tropsch synthesis (FTS). The FTS results clearly indicated that the selectivity towards long‐chain hydrocarbons was driven by the surface Na content, which promotes the CO dissociation and chain propagation. Additionally, it was shown that Fe3 O4, Fe5 C2 and Fe7 C3 coexist during FTS, revealing specific catalytic activity. As a result, a tandem mechanism was suggested for the CO2 conversion, consisting in a reverse water‐gas shift on Fe3 O4 followed by CO hydrogenation on the Fe carbides. Abstract : Na‐promoted Fe catalysts were investigated for the production of liquid fuel compounds using CO2 ‐based Fischer‐Tropsch synthesis. The surface Na content influenced the CO2 conversion and selectivity for long‐chain hydrocarbons.